2016
DOI: 10.1007/s11684-016-0482-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of ASIC3 and TRPV1 receptors in electroacupuncture-induced segmental and systemic analgesia

Abstract: Previous studies have demonstrated the effects of different afferent fibers on electroacupuncture (EA)-induced analgesia. However, contributions of functional receptors expressed on afferent fibers to the EA analgesia remain unclear. This study investigates the roles of acid-sensing ion channel 3 (ASIC3) and transient receptor potential vanilloid 1 (TRPV1) receptors in EA-induced segmental and systemic analgesia. Effects of EA at acupoint ST36 with different intensities on the C-fiber reflex and mechanical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…As a result, it is evident that, on visceral pain, EA-induced segmental analgesia is mediated by both A- and C-fibers, and extrasegmental analgesia is mediated only by C-fibers. Our results are consistent with previous studies on somatic pain that show that EA with a high enough intensity to excite Aβ-fibers is capable of producing local analgesia, but excitation of Aδ- and some C-fibers induces a more potent and extensive analgesia 7,20,21…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As a result, it is evident that, on visceral pain, EA-induced segmental analgesia is mediated by both A- and C-fibers, and extrasegmental analgesia is mediated only by C-fibers. Our results are consistent with previous studies on somatic pain that show that EA with a high enough intensity to excite Aβ-fibers is capable of producing local analgesia, but excitation of Aδ- and some C-fibers induces a more potent and extensive analgesia 7,20,21…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that the antinociceptive effects of EA treatment are different when EA is applied to acupoints with the same or different segmental innervation with the pain organs 79. For these experiments, EA stimulation was applied at contralateral PC 6, which innervates different segments of rectum and colon, to study the dose–effect relationship of EA at heterotopic acupoints on visceral nociception.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying EA induced segmental and extrasegmental analgesia are differ. Electrophysiological studies on somatic pain have shown that segmental analgesia of homotopic EA stimulation can be elicited by the activation of Aβ- and part of Aδ – fibers, whereas extrasegmental analgesia of heterotopic EA stimulation is only effective with intensities strong enough to excite Aδ–or C–fibers ( Xu et al, 2003 ; Zhu et al, 2004 ; Xin et al, 2016 ). It is very likely that SRD neurons are involved in the mechanism of the widespread extrasegmental antinociceptive effects of EA.…”
Section: Discussionmentioning
confidence: 99%
“…This experiment followed the protocol described by Beirith et al, 17 Experiments (ARRIVE). 20,21 Molecular docking analysis: in silico The structure of geraniol was obtained from PubChem (https://pubchem.ncbi.nlm.nih.gov/ compound/637566#section=Top) as a .sdf file. All receptors are coupled with an inhibitory ligand previously described in enzyme activity studies in vitro.…”
Section: Induction Of Orofacial Nociceptionmentioning
confidence: 99%